IMPLEMENTASI KEBIJAKAN PRO-POOR TOURISM DALAM MENINGKATKAN PEREKONOMIAN KOMUNITAS MASYARAKAT HAD BAI, THAILAND UTARA - Andredita, I Putu Sindhu; Kumala Dewi, Putu Ratih; Kawitri Resen, Putu Titah (DIKSHI (DISKUSI ILMIAH KOMUNITAS HUBUNGAN INTERNASIONAL), 2018)
ABSTRACT Tourism is one major source of income in term increasing benefit and opportunity for the poor, it will perpetually closed the gap between rich and poor in long period. This research will focus on the efforts of Thailand government in regard implement Pro-Poor Tourism. This policy has significant role regarding generate the revenue amongst the poor community in Thailand. However, during the process this policy has impacted only the upper and middle class in Thailand society, this in turn resulted a question about how should the decision maker in Thailand improved their tourism policy in terms to gain equal benefit amongst Thailand poor people and maximize their resources. Thailand government expects that the policy will unlock broader accses for the community to get direct involvement in tourism sector. Had - Bai is one of the village that selected to be the pilot project of Pro-Poor Tourism, hence, Thailand government’s strategy to evolve the village also as respond to the 1997 economic crisis. By implement intensively Pro-Poor Tourism through One Tambon One Product (OTOP) project policy, the brand new chapter of tourism agenda in Thailand has started Key words: Pro-Poor Tourism, One Tambon One Product (OTOP), Local community resources.